Adsorption Separation of Methyl Chloride from Nitrogen Using ZSM-5 and Mesoporous SBA-15 - Isil Toreci; F. Handan Tezel; Yang Yong; Abdelhamid Sayari (Adsorption Science & Technology)
The adsorption capacities of zeolite ZSM-5 and periodic mesoporous molecular sieve SBA-15 towards methyl chloride (chloromethane) and nitrogen were examined for the separation of these gases. Adsorption isotherms were obtained by using a constant volume technique up to 1.6 atm over the temperature range 40–80°C. The Langmuir, Freundlich, Sips and Toth adsorption models were fitted to the isotherms and validations of these models were discussed. Adsorption isosteres were obtained by using the parameters of the Toth equation. Binary adsorption isotherm predictions were undertaken using the Extended Langmuir (EL) and Ideal Adsorbed Solution Theory (IAST) in order to obtain a better understanding of the separation of methyl chloride from air. Henry's law constants, heats of adsorption and separation factors for both adsorbents were also obtained.